Proyecto Regional de Frijol del CIAT para la Zona Andina (PROFRIZA). Informe de actividades y resultados en 1990-91 - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1991)
Information is given of the major activities and results of the Regional Bean Program for the Andean Zone in 1990-91. Aspects studied involved participative research, small-scale seed production, integrated control of anthracnose, Ascochyta, and root rots, intercropping systems, strategies for pest management and control, and consumption promotion. The bean research and technology transfer network was also strenghtened. (CIAT)